The Role of the High-Sensitivity C-Reactive Protein in Patients with Stable Non-Cystic Fibrosis Bronchiectasis - Meng-Heng Hsieh; Yueh-Fu Fang; Guan-Yuan Chen; Fu-Tsai Chung; Yuan-Chang Liu; Cheng-Hsien Wu; Yu-Chen Chang; Horng-Chyuan Lin (Pulmonary Medicine)
Study Objectives. The aim of this study is to investigate the correlation between serum high-sensitivity C-reactive protein (hs-CRP) and other clinical tools including high-resolution computed tomography (HRCT) in patients with stable non-CF bronchiectasis. Design. A within-subject correlational study of a group of patients with stable non-CF bronchiectasis, who were recruited from our outpatient clinic, was done over a two-year period. Measurements. Sixty-nine stable non-CF bronchiectasis patients were evaluated in terms of hs-CRP, 6-minute walk test, pulmonary function tests, and HRCT. Results. Circulating hs-CRP levels were significantly correlated with HRCT scores (n=69, r=0.473, P<0.001) and resting oxygenation saturation (r=-0.269, P=0.025). HRCT severity scores significantly increased in patients with hs-CRP level of 4.26 mg/L or higher (mean ± SD 28.1±13.1) compared to those with hs-CRP level less than 4.26 mg/L (31.7±9.8, P=0.004). Oxygenation saturation at rest was lower in those with hs-CRP level of 4.26 mg/L or higher (93.5±4.4%) compared to those with hs-CRP level less than 4.26 mg/L (96.4±1.6%, P=0.001). Conclusion. There was a good correlation between serum hs-CRP and HRCT scores in the patients with stable non-CF bronchiectasis.